LITERATURE REVIEW: EVALUASI PENGELOLAAN LINEN DI RUMAH SAKIT - Ningtias, Dyah Ayu Ratna; Asih, Akas Yekti Pulih; Fasya, Abdul Hakim Zakiy (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
The hospital is a health service facility, a gathering place for sick and healthy people, a place for disease transmission and allows for environmental pollution and health problems.Hospitals need to take the right action in terms of linen management in the laundry unit in the hospital.Literature reviewThis study aims to determine the evaluation of linen management in hospitals.This study uses a literature review method with the data sources used are from Google Scholar and the Garuda portal with the keywords: Management of linen in hospitals. After screening, 15 articles were obtained which became the material for the analysis of this study. The results of the literature review showed that 2 out of 15 journals did not examine the evaluation of hospital linen management, 4 of 15 journals stated that the evaluation results of linen management were good and 9 of 15 journals stated that the evaluation results of linen management were not good. The conclusion of this study is that there are still many linen management processes in hospitals that are not in accordance with hospital SOPs and existing laws and regulations. It is necessary to apply more linen management processes and procedures throughout the hospital so as not to harm the environment and other parties. It is necessary to add HR insight in the laundry section regarding linen management so that linen management runs well and according to existing SOPs. Therefore, it is expected that each hospital, especially the management of linen in the laundry installation, must adjust the existing SOPs with the Decree of the Minister of Health of the Republic of Indonesia No. 1204 of 2004 concerning environmental health requirements. The laundry unit coordinator must be more stringent in supervising the laundry staff so that they always use PPE when working so that there are no work accidents when managing linen. 1204 of 2004 concerning environmental health requirements. The laundry unit coordinator must be more stringent in supervising the laundry staff so that they always use PPE when working so that there are no work accidents when managing linen. 1204 of 2004 concerning environmental health requirements. The laundry unit coordinator must be more strict in supervising the laundry staff so that they always use PPE when working so that there are no work accidents when managing linen.